Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

Long-Term Spatiotemporal Characteristics of Ulva prolifera Green Tide and Effects of Environmental Drivers on Its Monitoring by Satellites: A Case Study in the Yellow Sea, China, from 2008 to 2023 - Yating Zhan; Zhongfeng Qiu; Yujun Wang; Yiming Su; Yin Li; Yanmei Cui; Shuai Qu; Peng Wang; Xin Rong (Journal of Marine Science and Engineering, 2024)
Ulva prolifera (U. prolifera) green tide outbreaks have occurred in the Yellow Sea of China for many years, causing serious losses to marine ecology and the marine economy. The monitoring and tracking of U. prolifera green tide is a crucial aspect of marine ecological disaster prevention and control management. This paper aims to investigate the spatiotemporal distribution changes in U. prolifera green tide in the Yellow Sea throughout its life cycle. A survey of the Yellow Sea from 2008 to 2023 was conducted using multi-source remote sensing images. Long-term monitoring and analysis of U. prolifera revealed the evolution process of the green tide, including the early development, outbreak, decline, and extinction stages, considering time, space, and frequency of occurrence. Additionally, this study examined peak coverage change patterns over the past 16 years and analyzed the influence of environmental factors such as sea surface temperature and sea surface wind field on the development of U. prolifera. The research results serve as a valuable reference for the monitoring, early warning, and scientific prevention and control of U. prolifera green tide in the Yellow Sea, as well as other similar marine disaster areas.

Fabrication of compact zein-chondroitin sulfate nanocomplex by anti-solvent co-precipitation: Prevent degradation and regulate release of curcumin - Yufan Shi; Shuang Rong; Tingxian Guo; Ruyi Zhang; Duoxia Xu; Yahong Han; Fuguo Liu; Jiaqi Su; Hongxin Xu; Shuai Chen (Food Chemistry, 2024)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

The phylogeny analysis of MyoG gene in different pig breeds - Li Zhu; Xue-Wei Li; Su-Rong Shuai; Ming-Zhou Li; Lei Chen; Yi-Ren Gu; Kai Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)